Competition and Cooperation in Economics and Business - Lindawati Gani; Beta Y. Gitaharie; Zaäfri A. Husodo; Ari Kuncoro (Routledge, Taylor & Francis Group, 2018)
Asia and the Pacific have become the growth engine of the world economy with the contribution of two-third of the global growth. The book discusses current issues in economics, business, and accounting in which economic agents, as individuals, entrepreneurs and professionals, as well as countries in the Asia and Pacific regions compete and collaborate with each other and with the rest of the globe. Areas covered in the book include economic development and sustainability, labor market competition, Islamic economic and business, marketing, finance, accounting standard compliances, and taxation. It will help shed light on what business and economic scholars in regions have done in terms of research and knowledge development, as well as the new frontiers of research that have been explored and opening up.
Keywords: 330